Investigating the effect of a brief period of praying in emotional suppression situation on mood and ego depletion - Nemat Allah Yarollahi; Mohammad Reza Shairi; Zeynab Hasanzadeh Dastjerdi (Shahid Beheshti University of Medical Sciences, 2019)
For downloading the full-text of this article please click here. Background and Objective: According to the strength model, self-control is a finite resource that determines the capacity for effortful control over dominant responses and, once expended, leads to impaired self-control task performance, known as "ego depletion". The aim of the present study was to investigate the influence of a brief period of praying in situation of emotional suppression on ego depletion and mood in non-clinical samples. Method: To achieve this goal, an experimental study was conducted. A total number of 32 students were selected to participate in the experiments via multi-stage cluster sampling, and were randomly assigned to two emotional suppression/ prayer (experiment) and control/control (control) groups. Participants took part in individual sessions. First, they completed several questionnaires such the General Health (GHQ-12), Religious Attitude Scale-Revised (RAS-R), emotion regulation, Brunel Mood Scale (BRUMS-32) and stroop task (pre-tests). Then, each individual watched three negative clips while he/she was asked to suppress the emotions that might be elicited from clips (experimental group) or just watch them naturally (control group). Next, the experiment group was engaged in personal prayer manipulation, whereas the control group didn't do anything. Finally, the mood (BRUMS-32) and self-control performance (stroop task) of all participants were measured again. All ethical issues were observed in this study and the researchers declared no conflict of interests. Results: After the end of the experiments, the results didn't show any significant difference between the two groups in self-control performance. In addition, both groups reported similar levels of negative mood, but those who first suppressed their emotions and then prayed had greater positive mood compared to the control group. Conclusion: The results showed that individuals who used a combination of emotional suppression and prayer while being exposed to negative emotions showed higher positive mood, and had more vigor, calmness and happiness compared to those who behaved naturally. For downloading the full-text of this article please click here.